Marcela Ternavasio, Gobernar la Revolución. Poderes en disputa en el Río de la Plata, 1810-1816. Buenos Aires: Siglo XXI, 2007, 295 p. ISBN: 9789871220960. - Molina, Eugenia (2007)
Fil: Molina, Eugenia. Universidad Nacional de Cuyo